An examination of the emergence of Faydah at-Tijaniyyah in Ilorin, Nigeria - Solagberu, Abdur-Razzaq Mustapha Balogun (Ilorin journal of religious studies, 2018)
The work examines the history of Faydah at-Tijaniyyah (Divine Flood of the Tijaniyyah Order) in Ilorin. A spiritual transformation which the founder of the Tijaniyyah Sūfī Order, Shaykh Ahmad at-Tijani (d. 1815 C.E) prophecised Shaykh Ibrahim Niyass (d. 1975CE) proclaimed himself to be the person blessed with such position, and spread it across West Africa cities including Ilorin, Nigeria. The objective of this research it to fill the gap created in the history of Tijaniyyah Sūfī Order in Ilorin. The method of the research is based on both participatory observation and interpretative approach of relevant materials. The paper concludes that the advent of Faydah at-Tijaniyyah to Ilorin was due to many factors,and brought about a new understanding on the Tijaniyyah Order.Keywords: Tijaniyyah, Sūfī, Tariqah, Khalifah, Faydah at-Tijaniyyah